Covid and Competition: The Role of Competition Law and Regulation in ASEAN During and After the Pandemic - Burgess, Rachel; Schaper, Michael; McCarthy, Benjamin (Nova Science Publishers, 2022)
Do regulatory structures and competition laws have a role to play in helping businesses recover from Covid-19? Such policy issues are important, as the pandemic has had a major impact on the competitive capacity of the small and medium-sized enterprise (MSME) sector in Southeast Asia, which accounts for a majority of all operating businesses and employs over 140 million people in the region. Both competition policymaking and MSME policy are vital to the Southeast Asian community. This chapter provides an overview of what competition policy and law is, how it has been administered in the region, and how the COVID-19 pandemic has changed the business operating and competition environment. It also discusses how competition agencies have dealt with the challenges of Covid-19 so far. The chapter concludes with recommendations as to how these two different areas of public policy – those relating to competition, and those relating to MSME development – can work together to support recovery from the pandemic. Rather than proposing the enactment of new laws, it is suggested that there be greater collection of MSME data, and further development of consultative mechanisms with the small firm sector and industry associations, as well as the recruitment of staff with firsthand knowledge of MSMEs.